CULTURAL PRACTICES OF FOUR ELEMENTARY SCHOOL TEACHERS - Suficier, Darbi Masson; Muzzeti, Luci Regina [UNESP]; Castro Leao, Andreza Marques de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This article analyzes the cultural practices of four teachers from the early years of elementary school. Based on the Bourdieusian notion of practice, we seek to understand the preferences related to: cultural outputs, cultural consumption, reading, music, plastic arts, TV, cinema and writing; In addition to aspects of leisure and sociability. Data were collected through long-term semi-directive interviews and presented in the form of individual cultural profiles. The cultural practices of the professors interviewed have limitations in relation to access by different contexts, such as the place of residence, family income and lack of knowledge or limited knowledge in relation to the fruition of some practices.
Keywords: Cultural practices; Teacher; Elementary school